Generation of ultra-short pulse lasers using graphene and topological insulator based 2D nanomaterials / Hazlihan Haris - Hazlihan , Haris (2018)
In this work, fabrication of passive Saturable absorbers (SA) using 2D nanomaterials such as Graphene and Topological insulator (TIs) based was demonstrated. The fabricated passive SA was integrated in an Ytterbium-Doped Fiber Laser (YDFL) and Erbium-Doped Fiber Laser (EDFL) system for a ultra-short pulsed laser generation via mode-locking. UV-Vis-NIR spectrophotometer, Raman spectroscopy and Field Emission Scanning Electron Microscopy (FESEM) were used to verify the existence and investigate the optical properties of the fabricated SA. The SA was also characterized for nonlinear optical properties to study the SA parameters such as saturation intensity, modulation depth and non-saturable loss. The fabricated SA was applied to the end facet of a fiber ferrule, which was then mated to another clean ferrule connector to act as a passive SA, which was integrated into a ring YDFL and EDFL for pulsed laser generation. In addition, by using the Graphene SA into the YDFL cavity, a stable pulse laser was generated at 1052.89 nm wavelength with repetition rate of 4.5 MHz and pulse energy of 1.52 nJ. Next, mode locked YDFL with graphene oxide SA was generated at 1053 nm wavelength with repetition rate of 6 MHz and pulse energy of 1.65 nJ. An operating wavelength of approximately 1051 nm was generated when TI based SA (Bi2Se3) was used as a Mode-locker in a passively Mode-locked YDFL. Repetition rates is 8.3 MHz while a pulse energy of 1.5 nJ was recorded by using TI Bi2Se3 as SA. A stable Mode-locking operation was successfully obtained at the central operating wavelength of YDFL dropped from the initial 1050.28 nm with the addition of TI Bi2Te3 SA. The repetition rate of 9.5 MHz and pulse energy was 2.14 nJ. Ultra-short pulses beyond 1.5 μm region wavelength with durations below 200 fs were generated through a Mode-locked in EDFL seeded by used fabricated SA. A stable passive Mode-locked EDFL operating at 1565 nm wavelength demonstrated using graphene SA as Mode-locker. In anomalous regime with estimated group delay dispersion, GDD of -0.22 ps2, the soliton mode locked EDFL pulse was generated with repetition rate of 20.7 MHz, pulse width of 0.88 ps and pulse energy of 1.5 nJ. A stable bound soliton appeared at wavelength 1564 nm with inserting about 13.2 m single mode fiber, SMF into EDFL cavity. In the particular case there were 7 solitons in bunch with repetition rate of 11.9 MHz and anomalous regime GDD of -0.37 ps2. The pulse width of 1.04 ps and pulse energy of 1.97 nJ by using passively graphene SA as SA. Other fabricated SA (graphene oxide, TI bismuth selenide and TI bismuth telluride) were used to reliably Mode-locked erbium soliton fiber lasers producing picosecond pulses at 1.56 μm. Various modes of pulse operation were studied using the above mentioned SA. Soliton mode-mocking was realized using graphene and TIs based SA